Research of Optimal Arrangement of Sensor for Wind Turbine Gearbox based on Immune Algorithm - Song Zhongyue; Li Haiyang; Ma Jiaojiao; Zhen Dong; Shi Zhanqun; Shen Zhaoyang (Jixie chuandong)
The signal acquisition is a prerequisite for fault analysis and diagnosis,but also the necessary condition in the fault diagnosis of wind turbine gearbox. At present,the most mature method is vibration signal analysis method,however,because the internal structure of the gearbox can not be destroyed,it can only lead to vibration sensor installed on the external wall of the gearbox. The sensors arrangement of gearbox will directly influence the quality of diagnostic accuracy. By using the immune algorithm to solve the problem of sensor arrangement in fault diagnosis of wind turbine,the gearbox vibration source coordinates is constructed,the optimal acquisition path of vibration transmission is calculated,the best measuring point is determined. The placement optimization of the measuring point for sensor is realized,an effective method for sensor arrangement is provided.